The abnormalities in the coagulation factory in patients with essential hypertension and relationship between the coagulation abnormalities and end organ damage - Celebi, Harika; Karaca, Ilgin; Ilkay, Erdo?an; Tamer, Ali; Koc, Zuhal (My University, 2005)
Hypertension is one of the important health problems in the world due to its high incidence and the fact that it causes mortality and morbidity. Mortality and morbidity in hypertensive patients are caused by damage of the target organ. Hypertensive patients are found to have impairments in coagulation mechanism in comparison to normotensive people. The relation between coagulation abnormalities in hypertensives and damage of the target organ is debatable. In this study we investigated coagulation abnormalities in hypertensive patients and the relation between the possible abnormality and target organ damage. Prothrombin time, partial thromboplastin time, fibrinogen, D-dimer and antithrombin III were measured in 50 essential hypertension patients and 50 normotensive controls. Target organ damage was assessed by clinical evaluation and laboratory tests including measurement of creatine clearance, proteinuria, ophthalmoscopy, electrocardiography, echocardiography, and ultrasound examination of major arteries. Plasma fibrinogen and D-dimer levels were significantly greater in hypertensives than normotensive controls. Antitrombin III level was significantly lower in hypertensives than controls. Hypertensive patients had greater body mass index and triglyceride and LDL cholesterol levels and lower HDL cholesterol than controls. The difference in terms of impairment of coagulation parameters was not statistically significant between hypertensive cases with target organ damage and hypertensive cases without target organ damage. Elevated plasma levels of fibrinogen, D-dimer and lower level of AT III in patients with essential hypertension may contribute to the development of atherosclerotic disease. Copyright © Hellenic Society of Haematology.
Keywords: Antithrombin III; D-dimer; Fibrinogen; Hypertension; Target organ damage